The integrals in Gradshteyn and Ryzhik. Part 3: Combinations of logarithms and exponentials - Moll, Victor H. (Scientia Series A: Mathematical Sciences, 2025)
We present the evaluation of a family of exponential-logarithmic integrals. These have integrands of the form \(P(e^tx · x)\) where \(P\) is a polynomial. The examples presented here appear in sections 4.33, 4.34 and 4.35 in the classical table of integrals by I. Gradshteyn and I. Ryzhik.